2022
DOI: 10.1371/journal.pone.0274488
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro neurotoxicity and myotoxicity of Malaysian Naja sumatrana and Naja kaouthia venoms: Neutralization by monovalent and Neuro Polyvalent Antivenoms from Thailand

Abstract: Naja sumatrana and Naja kaouthia are medically important elapids species found in Southeast Asia. Snake bite envenoming caused by these species may lead to morbidity or mortality if not treated with the appropriate antivenom. In this study, the in vitro neurotoxic and myotoxic effects N. sumatrana and N. kaouthia venoms from Malaysian specimens were assessed and compared. In addition, the neutralizing capability of Cobra Antivenom (CAV), King Cobra Antivenom (KCAV) and Neuro Polyvalent Antivenom (NPAV) from Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…All deaths were due to a monocled cobra bite. An in vitro study found that the neurotoxic and myotoxic effects of N. kaouthia venom were more potent than those of N. sumatrana venom [39], which is consistent with our finding that neurological effects were more common in patients bitten by a monocled cobra than in those bitten by either of the spitting cobras. Our data suggest that patients who had been bitten by a cobra, whether of the monocled or spitting variety, should be monitored closely for neurological effects and respiratory symptoms, with prompt management should they occur.…”
Section: Discussionsupporting
confidence: 91%
“…All deaths were due to a monocled cobra bite. An in vitro study found that the neurotoxic and myotoxic effects of N. kaouthia venom were more potent than those of N. sumatrana venom [39], which is consistent with our finding that neurological effects were more common in patients bitten by a monocled cobra than in those bitten by either of the spitting cobras. Our data suggest that patients who had been bitten by a cobra, whether of the monocled or spitting variety, should be monitored closely for neurological effects and respiratory symptoms, with prompt management should they occur.…”
Section: Discussionsupporting
confidence: 91%
“…In the same year, Barfaraz and Harvey successfully utilized the chick biventer cervicis nerve–muscle preparation to compare the relative potencies of six different antivenoms for neutralization of neurotoxic and myotoxic proteins present in six distinct snake venoms ( Barfaraz and Harvey, 1994 ). The chick biventer cervicis nerve–muscle preparations, along with mouse phrenic nerve-diaphragm preparations, have since then been employed to evaluate the efficacy of antivenoms in neutralizing the neuromuscular blocking effect induced by various venoms ( Fry et al, 2001 ; Camargo et al, 2011 ; Kornhauser et al, 2013 ; Herrera et al, 2016 ; Silva et al, 2017 ; Madhushani et al, 2020 ; Zukifli et al, 2022 ).…”
Section: Electrophysiology In Antivenom Researchmentioning
confidence: 99%